LaTeX graphics with TikZ : a practitioner's guide to draw 2D and 3D images, diagrams, charts, and plots - Kottwitz, Stefan (Packt Publishing Ltd., 2023)
Unleash the power of LaTeX to create professional text, articles, diagrams, and charts using TikZ and its wide range of features for stunning 2D and 3D effects Purchase of the print or Kindle book includes a free PDF eBook Key Features Achieve native construction of images and diagrams in your LaTex theses, articles, or books with enhanced quality Discover comprehensive explanations and real-world use cases to apply in your own endavors Explore customizations and tweaks to grasp the synergy of LaTeX and TikZ graphics Book Description In this first-of-its-kind TikZ book, you'll embark on a journey to discover the fascinating realm of TikZ--what it's about, the philosophy behind it, and what sets it apart from other graphics libraries. From installation procedures to the intricacies of its syntax, this comprehensive guide will help you use TikZ to create flawless graphics to captivate your audience in theses, articles, or books. You'll learn all the details starting with drawing nodes, edges, and arrows and arranging them with perfect alignment. As you explore advanced features, you'll gain proficiency in using colors and transparency for filling and shading, and clipping image parts. You'll learn to define TikZ styles and work with coordinate calculations and transformations. That's not all! You'll work with layers, overlays, absolute positioning, and adding special decorations and take it a step further using add-on packages for drawing diagrams, charts, and plots. By the end of this TikZ book, you'll have mastered the finer details of image creation, enabling you to achieve visually stunning graphics with great precision. What you will learn Understand the TikZ language and how to use its libraries and packages Draw geometric shapes with text and add arrows, labels, and decorations Apply transformations and use transparency, shading, fading, and filling features Define styles and program with loops to streamline your code Build trees, graphs, and mind maps and draw easy curves with smooth transitions Produce block diagrams and flow charts to visualize process steps Generate line charts and bar charts to showcase your data Plot data sets and mathematical functions in two and three dimensions Who this book is for This book is for LaTeX users, including students and academic authors, seeking to incorporate figures such as diagrams, plots, and graphics to their theses, articles, and books. If you're familiar with LaTeX basics from beginner's books or tutorials, you'll be able to effortlessly explore the graphics topics in this book.